"Kashmiri Women in Politics: Driving Change in Jammu and Kashmir" - Shujaat Yousuf pirzada (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This paper examines the evolving role of Kashmiri women in the political arena of Jammu and Kashmir, a region historically characterized by conflict and patriarchal norms. Despite socio-political constraints and cultural barriers, women in the region have increasingly begun to assert their presence in electoral politics, grassroots activism, and policymaking. Tracing the journey from early pioneers like Begum Zaffar Ali to contemporary leaders such as Sakina Itoo and Shehla Rashid, the paper highlights the growing visibility and influence of women in shaping the political narrative. It also investigates the current trends, challenges, and prospects for women’s political empowerment, arguing that inclusive governance and gender-sensitive reforms are crucial for sustained democratic development in the region.